Corrosion Behavior of low carbon steel sheets for car bodies - Hamzah, Esah; Kanniah, Maiiyeaalagan (Faculty of Mechanical Engineering, Universiti Teknologi Malaysia, 2005)
This paper is a study on the corrosion behaviour and performance between coated and uncoated steel sheets which are used in car body manufacturing. The samples used are coated and uncoated steel plates taken from 3 different car models. ASTM B 117-90 Salt Spray (Fog) and ASTM D 2933-74 Corrosion Resistance of Coated Steel Specimens (Cyclic Method) corrosion test are carried out in order to study the corrosion behaviour and performance. The corrosion behaviour was determined by analyzing the surface and cross section of the samples by using scanning electron microscope whereas the corrosion performance was determined by mass loss method and visual examination. From the analysis it was found that for all three models the uncoated samples were attacked by uniform corrosion. Model 1 showed the best corrosion performance; followed by Model 2 and Model 3. The coating system for all three were able to protect the steel substrate from corrosive environment. However, blisters have formed on the surface of coated specimen of Model 3 after salt spray (fog) test which was due to the initial micro scratches on the coating.